2019
DOI: 10.1103/physrevc.100.064602
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of optical potential strengths in reactions on Sn120 involving strongly bound, weakly bound, and exotic nuclei

Abstract: We present new experimental angular distributions for the elastic scattering of 6 Li + 120 Sn at three bombarding energies. We include these data in a wide systematic involving the elastic scattering of 4,6 He, 7 Li, 9 Be, 10 B and 16,18 O projectiles on the same target at energies around the respective Coulomb barriers. Considering this data set, we report on optical model analyses based on the double-folding São Paulo Potential. Within this approach, we study the sensitivity of the data fit to different mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 59 publications
2
45
1
Order By: Relevance
“…This indicates that fusion is somehow favored for 10 B, while peripheral reaction channels, which are connected to strong surface absorption processes, are favored for the other weakly bound nuclei. This behavior seems to be connected to the projectile breakup energy threshold [15].…”
Section: Theoretical Calculationsmentioning
confidence: 88%
See 1 more Smart Citation
“…This indicates that fusion is somehow favored for 10 B, while peripheral reaction channels, which are connected to strong surface absorption processes, are favored for the other weakly bound nuclei. This behavior seems to be connected to the projectile breakup energy threshold [15].…”
Section: Theoretical Calculationsmentioning
confidence: 88%
“…Although the elastic scattering represents the most direct and simplest process concerning a nuclear reaction, its description can become extremely challenging if the effect of couplings to nonelastic channels is strong. Particularly, in nuclear collisions involving weakly bound or radioactive nuclei, direct processes, such as transfer or breakup, can affect the dynamics of the reaction due to their cluster structure and low breakup energy threshold [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In [43], Eq. ( 3) has been proposed to systematically study exotic and stable, tightly and weakly bound, nuclei projectiles ( 4,6 He, 6,7 Li, 9 Be, 10 B, 16,18 O) reacting on the same, 120 Sn, target nucleus, in a wide energy range.…”
Section: Ii1 São Paulo Potential (Spp)mentioning
confidence: 99%
“…We verified how data are most sensitive to the strength of the absorptive imaginary part, which tends to mostly vary as a function of the projectile binding energy (table I). Therefore, table I relies on projectiles studied in [43] and here. From [43], we concluded that lower the binding energy higher the absorptive imaginary strength, which tends to be meaningful even at longer interacting distances (R > 15 fm), mainly for describing reactions of stable weakly bound and exotic nuclei projectiles.…”
Section: Ii1 São Paulo Potential (Spp)mentioning
confidence: 99%
See 1 more Smart Citation